2015
DOI: 10.1017/s0021932015000371
|View full text |Cite
|
Sign up to set email alerts
|

Communication in the Context of Family Caregiving: An Exploratory Study of Ugandan Children on Antiretroviral Therapy

Abstract: SummaryIt is important to consider the complexities of family dynamics when deciding when and how to communicate with HIV-infected children about their illness and treatment. Previous research has focused on providers’ and caregivers’ perspectives on whether, when and how to disclose HIV/AIDS diagnosis and treatment to HIV-infected children. From the perspective of HIV-infected children, communication does not mean just giving information about illness and treatment, but also encompasses emotional and material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Mutumba, Bauermeister [102] describes how pill taking between HIV-positive parents and YPLHIV in Uganda fostered bonding "whenever she took hers, I also took mine". In contrast, in three studies, young women expressed the lack of support from caregivers [101,112,120]. Trusting relationships with family members were frequently described as important [101,102,109,121,122].…”
Section: B) Social Supportmentioning
confidence: 88%
See 1 more Smart Citation
“…Mutumba, Bauermeister [102] describes how pill taking between HIV-positive parents and YPLHIV in Uganda fostered bonding "whenever she took hers, I also took mine". In contrast, in three studies, young women expressed the lack of support from caregivers [101,112,120]. Trusting relationships with family members were frequently described as important [101,102,109,121,122].…”
Section: B) Social Supportmentioning
confidence: 88%
“…Caregivers in a South African study highlighted their lack of social support and how it hindered their ability to cope and subsequently support their children [104]. In three studies, YPLHIV articulated a deep longing for their deceased parents which authors indicated signified the importance parents played in nurturing belonging and its link with creating meaning in life [104,114,117,120]. Moreover, the yearning for one's father was interpreted as being underpinned by "cultural expectations of being cared for and finding a rightful place in their father's home" [114].…”
Section: B) Social Supportmentioning
confidence: 99%
“…For example, over the past decade, both physical and psychosocial health symptoms have been reported by these grandparents, including cardiovascular symptoms, increased emotional stress, burnout, fatigue, anger, resentment, guilt, anxiety, mental weariness and isolation (Drah, ; Grobler & Roos, ; Horwitz, Yogo, Juma, & Ice, ; Ice, Yogo, Heh, & Juma, ; Kamya & Poindexter, ; Kasedde et al, ; Littrell, Murphy, Kumwenda, & Macintyre, ; Osafo et al, ; Schatz & Gilbert, ; Sefasi, ; Shaibu, ). Most recent research has also examined the issues of HIV status disclosure (Kajubi, Katahoire, Kyaddondo, & Whyte, ) and care relationships among grandparents–grandchildren dyads (Rutakumwa, Zalwango, Richards, & Seeley, ).…”
Section: Introductionmentioning
confidence: 99%